Detailed Analysis of a Regenerative Active Clamping Snubber for a Phase-Shifted Converter - Dorin Petreus; Toma Patarau (IEEE Access)
The phase-shifted converter (PSFB) is one of the most used converters for applications where high power and galvanic isolation are required. To achieve zero voltage switching (ZVS) on the primary side these converters use the leakage inductance of the main transformer and the parasitic capacitances of the primary bridge MOSFET transistors. The higher this inductance is, the lower the output power that ensures ZVS. However, the resonant inductor, together with the parasitic capacitances of the secondary bridge and the transformer’s secondary winding, induce ringing and high voltage spikes at the secondary bridge output. To mitigate this problem snubber circuits are used. These converters’ maximum power depends on the energy stored in leakage inductances and parasitic capacitances, which relate to the choice of the snubber circuits used. The present paper analyzes in detail the behavior of an active clamp circuit. It determines the conditions for zero voltage turn ON of the snubber transistor thus improving the snubber’s efficiency and of the entire phase-shifted converter. All the results are validated through simulation and experimental models.